KEJAHATAN PENCUCIAN UANG (MONEY LAUNDERING): TINJAUAN UNDANG-UNDANG NOMOR 8 TAHUN 2010 TENTANG PENCEGAHAN DAN PEMBERANTASAN TINDAK PIDANA PENCUCIAN UANG - Yani, Mas Ahmad (E-Journal Widya Yustisia, 2017)
Pretension of Money laundring in Indonesia has started since the act no. 15, 2002 about pretension of money laundry changes into the act no. 15, 2003 and it shown a positive impact. Meanwhile, the act does not seem optimal. Therefore, the Indonesin parliament constructs another act which is act no.8, 2010 about prevention and pretension of money. The objective of this study is to discuss about how far the act no.8, 2010 about prevention and pretension of money laundry can be implemented effectively. The method used library study with descriptive, explorative and analytic approaching. It can be concluded that: 1. Occurs some criminal offense as it is limited implemented in the second clause of act no. 8, 2010 towards money laundry presumption, does not need pre verification as long as the money came from corruption with the record of 2 proof as the initial proof. 2. Money laundry in criminology is qualified as white collar criminalization, therefore using inverse method is relevant, but in the implementation it is depended on the judge’s will. The suggestion that, all the element of law enforcement and the criminal justice system should have well integration and dedication in this kind of cases meanwhile special skills regarding the financial system and the support from financial expert are needed.